AN ANALYSIS ON KETI AMENAT: A TRADITIONAL DIAGNOSTIC RITES OF THE SICK IN METO COMMUNITY OF NORTH CENTRAL TIMOR REGENCY - Fuamuni, Selfiana; Kamlasi, Imanuel; Bouk, Edmundus (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
The aims of this study are to find out the process of Keti Amenat ritual, and the meanings contained in this ritual. Method used in this study is descriptive qualitative method and the data collection techniques are recording and interview. The data obtained from informants, including Amnaneor the elders. Criteria specified as informants are people who have good knowledge and actively practice of Keti Amenat ritual. The result shows that the process consists of three stages: preparing the sick, offering animal sacrifice, and offering food to the spirits of ancestors. Meanings embodied in the ritual are religious meaning, social meaning, and magical meaning.